Accés à la terre et transhumance en Grèce : bien commun et conflits sociaux - Stavriani Koutsou; Athanassios Ragkos; Maria Karatassiou (Développement Durable et Territoires)
The governance of common lands, considered as a common good, has always been a matter of major importance for economy and social cohesion in rural areas. Indeed, they highly influence the sustainability of local production systems and guarantee social cohesion. In Greece, public rangelands constitute a common good for mountain-based rural societies, which are basically involved in livestock production as an economic activity, and access to rangelands conditions the economic viability of their activity. This concerns pertains mostly to extensive livestock systems, such as transhumance systems. Despite its important role, transhumance nowadays faces dangers that threaten its viability. These dangers are internal as well as external and they are the causes of social conflicts among farmers, as well as among farmers and other actors involved in the sector. The management of rangelands, which for centuries was ensured within the « tseligato » (a form of specific cooperative-type organization of livestock farmers), is nowdays today threatened by the individualistic behaviour of pastoralists, which is encouraged, to an extent, by policy measures. The central question that arises is to what extent these hazards and conflicts determine the sustainability of mountain rangelands and the sustainability of transhumance. It appears that, under current conditions, the mitigation of social conflicts can be achieved not only through targeted regulatory adjustments, at the central or regional level, but also through participatory approaches and the encouragement of local initiatives.